A Systematic Review: Trend Research of Polymer Thin Film Dosimetry - Susilawati Susilawati; Aris Doyan; Syarful Annam; Teguh Ardianto; Muhammad Ikhsan; Nurul Rachma Ardianti (Journal of Material Science and Radiation, 2025)
The application of polymer dose gels is limited by the sensitivity of dose readout methods and dose gel properties. It is a challenge to find suitable dosimeters for registration of doses delivered to the target by orthovoltage therapy units. The application of metal-particle-enriched polymer composites for dose registration in X-ray therapy might be an elegant solution, especially if recent dose-reading technologies exploring advantages of different physical phenomena are involved. This research aims to identify and analyze research trends of Polymer thin film dosimeters. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2016-2025 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research Polymer thin film dosimeters that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2016 to 2025 has experienced ups and down. There are many documents in the form of articles, chapters, proceeding, monograph, preprint, and edited books that discuss research into the polymer thin film dosimetry. Key words that are often used in research about it are Gamma radiation dosimetry, Polyvinyl alcohol, PVA, TeO2, ZnO, Polymerization, etc.